Investigation of the quality levels of foreign students who educate in DPU faculty of sports sciences and foreign students at different faculties - Soub, Anoud; Gulac, Meryem (Journal of Physical Education, 2025)
The aim of this study is to investigate the quality of life of foreign students studying at the Faculty of Sport Sciences and international students studying at different faculties at DPU. In this context, "University Quality of Life Scale" was applied to determine the quality of life of students. The research data were obtained from a total of 272 students studying at the Faculty of Sports Sciences, Faculty of Business Administration,Faculty of Education and Faculty of Engineering. One-way ANOVA test was used for data analysis. The quality of life of the students,faculty, gender,educational status, place of residence,leisure time, time of arrival in Turkey and finally welfare level were analyzed . The quality of life of the student differed significantly according to the faculty,gender,education level,place of residence,and leisure time. It was observed that there was no significant difference in the variables of arrival in Turkey and welfare level.